The Gas Kinematics of High Mass Star Forming Regions - Klaassen, Pamela D. (My University, 2008)
The mechanism by which massive stars form is not nearly as well understood as it is for lower mass stars. For instance, at the onset of massive star formation, it is still not clear whether the mass for a given massive star comes from the turbulent collapse of a dense core (i.e McKee & Tan, 2003) or whether the star continues to accrete material from the cores environment as it grows (i.e. Bonnell et al., 1998). From this point, it is suggested that the cold, massive core (an Infrared Dar Cloud) begins to heat up and form a Hot Core. Later in its protostellar evolution, an HII region forms from the ionizing radiation being produced by the massive star. How, or even whether, accretion onto the massive protostar can continue in the presence of the large outward thermal and radiation pressures from the star is also quite uncertain. Can the star continue to accrete ionized gas (i.e. Keto & Wood, 2006)? Are the accretion rates high enough early on to account for the final observed masses (i.e. Klaassen et al., 2006)? Or, is there some way of minimizing the radiation pressure affecting the infalling gas (i.e. McKee & Ostriker, 2007, and references therein). Here, we present observations which suggest that there is a statistically significant, although short, period in which rotation and infall of molecular gas (which powers a bipolar outflow) continue after the formation of an HII region. This continued infall of material is seen on both large and small scales, and appears to be continuing to produce outflows in many of the sources observed in this study. That it is not seen in all sources suggests that this stage is short lived.
Keywords: massive star formation; Infrared Hot Core; protostar; accretion; HII region